Solitary Fibrous Tumors of the Chest: An Analysis of Fifty Patients - Zhang, Jingwen; Liu, Jumin; Zhang, Zhihao; Tian, Beizong (Frontiers in Oncology, 2021)
Background: A solitary fibrous tumor of the chest (SFTC) is a subtype of solitary fibrous tumor (SFT) with a low incidence rate. The purpose of this study is to analyze the diagnosis and treatment of SFTC and the difference between benign and malignant solitary fibrous tumor of the pleura (SFTP) to improve the understanding of this rare disease. Methods: A retrospective analysis of fifty patients with SFTC (33 cases in the pleura and 17 in the lung) was performed. Clinical and imaging characteristics, pathological features, and treatment follow-up outcomes were analyzed. Results: The common symptoms of the 50 patients included a cough, expectoration, chest tightness, fever, and chest pain. Space occupying lesions were found via plain computed tomography (CT) and enhanced CT was used for enhancement of the tumors. It was also found that 18 cases had necrosis, and 5 cases had calcification. The histopathology results showed that frequent nuclear division, obvious morphological variation, necrosis, and the high expression of Ki-67 cells are markers of malignant SFTC. There were significant differences in age, chest tightness, necrotic foci in CT, and expression of Ki-67 between the benign and malignant SFTP cases. All the patients who received treatment were given an excellent prognosis. Conclusion: A combination of enhanced CT, histopathology, and immunohistochemistry can be used for the accurate diagnosis of SFTC. Advanced age, chest tightness, necrotic foci in CT, and a high Ki-67 index were more likely to be malignant SFTP. Operation and radiofrequency ablation can provide favorable outcomes for both benign and malignant SFTC.